Wolfram Lacher. (2018). Tripoli’s Militia Cartel: How Ill-Conceived Stabilisation Blocks Political Progress, and Risks Renewed War No. (20) April - Kazan, Abdullah; Salem Margin, Hussein (Jordan Journal of Social Sciences, 2023)
Unifying different social theories under one Grand Theory, or in accordance with a unified Sociological Perspective, has been an ongoing endeavor within the theoretical and academic heritage of Sociology. This research argues that the “Complex Cognitive Models” as shaped by “Abdelwahab Elmessiri”, and as represented through his concepts of “Comprehensive Secularism” and “Transfer”, are all together a valid theoretical framework. This framework through which Social Theories, or the so called “Grand Approaches” of Sociology as addressed by “Jacques Herman” in his book “Les Lanages De La Sociologie”, can be unified, and can subsequently resolve any nominal conflicts or contradictions between these theories and approaches.